2023
DOI: 10.3389/fnins.2023.1021152
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the brain and retina after traumatic injury

Abstract: The brain and the retina share many physiological similarities, which allows the retina to serve as a model of CNS disease and disorder. In instances of trauma, the eye can even indicate damage to the brain via abnormalities observed such as irregularities in pupillary reflexes in suspected traumatic brain injury (TBI) patients. Elevation of reactive oxygen species (ROS) has been observed in neurodegenerative disorders and in both traumatic optic neuropathy (TON) and in TBI. In a healthy system, ROS play a piv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 111 publications
0
15
0
Order By: Relevance
“…The pathomechanisms potentially involved in RGC death include the disruption of the blood-brain barrier, leading to the infiltration of activated immune cells such as macrophages and neutrophils. These immune cells produce a significant amount of reactive oxygen species (ROS) and cytokines, further activating microglia and causing damage to mitochondria and endoplasmic reticulum [475][476][477]. Numerous studies on murine and rodent models of TON have demonstrated an overproduction of ROS [478][479][480], as well as a decrease in the antioxidant activity of SOD [478], and CAT [481,482].…”
Section: Pathogenesis Of Traumatic Optic Neuropathies: Role Of Oxidat...mentioning
confidence: 99%
See 3 more Smart Citations
“…The pathomechanisms potentially involved in RGC death include the disruption of the blood-brain barrier, leading to the infiltration of activated immune cells such as macrophages and neutrophils. These immune cells produce a significant amount of reactive oxygen species (ROS) and cytokines, further activating microglia and causing damage to mitochondria and endoplasmic reticulum [475][476][477]. Numerous studies on murine and rodent models of TON have demonstrated an overproduction of ROS [478][479][480], as well as a decrease in the antioxidant activity of SOD [478], and CAT [481,482].…”
Section: Pathogenesis Of Traumatic Optic Neuropathies: Role Of Oxidat...mentioning
confidence: 99%
“…Taken together, many publications gathered evidence on promising preclinical results in animal models of optic nerve trauma. However, an important factor to be considered for practical uses of antioxidants after optic nerve trauma in humans is the prompt administration of the drug after diagnosis [475]. A delay in this context may equivale to unsuccessful effect of the medication, due to early activation of intracellular downstream transductions [475].…”
Section: Potential Antioxidants For Traumatic Optic Neuropathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 9 ] To date, the exact mechanism of secondary degeneration is not fully understood, but it is believed to involve complex interactions between inflammation, oxidative stress, and cell apoptosis. In recent years, increasing evidence has suggested that RGC damage is dependent on the imbalanced production and elimination of reactive oxygen species (ROS), [ 1,10–12 ] mainly hydrogen peroxide (H 2 O 2 ), hydroxyl radical (•OH), singlet oxygen ( 1 O 2 ), and superoxide anions (O 2 •− ). [ 13,14 ] In addition, reactive nitrogen species (RNS), especially nitric oxide (NO), can react with the free radical superoxide and contribute to neuronal cell damage in the retina.…”
Section: Introductionmentioning
confidence: 99%